2018
DOI: 10.1172/jci.insight.121522
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous retrovirus expression is associated with response to immune checkpoint pathway in clear cell renal cell carcinoma

Abstract: Although a subset of clear cell renal cell carcinoma (ccRCC) patients respond to immune checkpoint blockade (ICB), predictors of response remain uncertain. We investigated whether abnormal expression of endogenous retroviruses (ERVs) in tumors is associated with local immune checkpoint activation (ICA) and response to ICB. Twenty potentially immunogenic ERVs (πERVs) were identified in ccRCC in The Cancer Genome Atlas data set, and tumors were stratified into 3 groups based on their expression levels. πERV-high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
157
3
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(167 citation statements)
references
References 30 publications
(41 reference statements)
5
157
3
2
Order By: Relevance
“…51 Besides virally driven tumors (e.g., MCC and HPV-derived malignancies), 20 potentially immunogenic endogenous retroviruses have recently been reported in clear-cell renal cell carcinoma patients. 52 These findings may explain why renal tumors are immunogenic (i.e., respond well to PD-1 blockade 53,54 or to interleukin-2 55 ), in spite of not having a particularly high mutation prevalence. 56 Interestingly, L19-mIL12 triggered a local intratumoral increase of Tregs in LLC lesions, but not in CT26 tumors.…”
Section: Discussionmentioning
confidence: 99%
“…51 Besides virally driven tumors (e.g., MCC and HPV-derived malignancies), 20 potentially immunogenic endogenous retroviruses have recently been reported in clear-cell renal cell carcinoma patients. 52 These findings may explain why renal tumors are immunogenic (i.e., respond well to PD-1 blockade 53,54 or to interleukin-2 55 ), in spite of not having a particularly high mutation prevalence. 56 Interestingly, L19-mIL12 triggered a local intratumoral increase of Tregs in LLC lesions, but not in CT26 tumors.…”
Section: Discussionmentioning
confidence: 99%
“…When considering human tumors, Miller et al have reported that polyomavirus-specific T cells may represent up to 21% of the T cell specificities within the tumor mass of Merkel Cell Carcinoma (MCC) 53 . Besides virally-driven tumors (e.g., MCC and HPV-derived malignancies), twenty potentially immunogenic endogenous retroviruses have recently been reported in clear-cell renal cell carcinoma patients 54 . These findings may explain why renal tumors are immunogenic (i.e., respond well to PD-1 blockade 55, 56 or to interleukin-2 57 ), in spite of not having a particularly high mutation prevalence 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that a subset of human tumors have abnormal expression of these repetitive RNAs, including ERVs, which leads to the activation of innate immune signaling and upregulation of immune checkpoint genes (Rooney et al 2015, Smith et al 2018, Solovyov et al 2018, Panda et al 2018a). Our research group and others have recently found that ERV expression is associated with evidence of immune checkpoint gene expression and T cell infiltration in several cancers including ccRCC, a cancer with a significant response to immune checkpoint therapy despite having a relatively low TMB (Panda et al 2018a, Rooney et al 2015, Smith et al 2018). Expression of ERVs was found to correlate well with response to ICB in patients with urothelial cancer and patients with ccRCC (Panda et al 2018a, Solovyov et al 2018.…”
Section: Expression Of Repetitive Rnasmentioning
confidence: 99%